TAIGA-A hybrid array for high-energy gamma astronomy and cosmic-ray physics - Budnev, N; Astapov, II; Bezyazeekov, PA; Borodin, A; Bruckner, M; Chernykh, D; Chiavassa, A; Dyachok, A; Fedorov, O; Gafarov, A; Garmash, A; Grebenyuk, V; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The combination of a wide angle timing Cherenkov array and Imaging Atmospheric Cherenkov Telescopes operated in mono mode offers a cost-effective way to construct a few square kilometers array for ultrahigh-energy gamma astronomy. The first stage of the TAIGA Observatory (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) is described here. It will comprise TAIGA-HiSCORE - 120 wide angle Cherenkov stations distributed over an area of 1.0 km(2) and three IACTs (TAIGA-IACT).